Death by design : capital punishment as social psychological system - Haney, Craig (American Psychology-Law Society series., 2005)
How can otherwise normal, moral persons - as citizens, voters, and jurors - participate in a process that is designed to take the life of another? In DEATH BY DESIGN, research psychologist Craig Haney argues that capital punishment, and particularly the sequence of events that lead to death sentencing itself, is maintained through a complex and elaborate social psychological system that distances and disengages us from the true nature of the task. Relying heavily on his own research and that of other social scientists, Haney suggests that these social psychological forces enable persons to eng.